Bovine reproduction - Hopper, Richard M. 1954- (Hoboken, New Jersey Wiley-Blackwell, 2021)
The newly revised Second Edition of Bovine Reproduction delivers a comprehensive overview of all major issues in bovine reproduction. Written by leading experts in the subject, the book is an indispensable reference for any veterinarian dealing with bovine fertility. Bovine Reproduction is divided into sections on the bull, the cow, the neonate, and assisted reproduction techniques. New chapters cover new gene manipulation technologies, managing problem donors, lameness, and more. Outdated and redundant information from the First Edition has been removed and replaced by coverage of new diseases, technologies, procedures, techniques, and approaches to fertility problems. A new companion website provides images and tables from the book in PowerPoint format. A practical and comprehensive reference, Bovine Reproduction is a must-have purchase for bovine practitioners, theriogenologists, animal scientists, veterinary students, and residents with an interest in cattle"--
Includes bibliographical references and index.
Keywords: Reproduction; Cattle -- physiology; Pregnancy -- Complications -- Veterinary service; Reproductive health -- methods; Reproductive technology -- Veterinary service